Peran Big Data dalam Pengambilan Keputusan Pemasaran di Era Digital - Ibrahim, Darmawansah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the role of big data in supporting marketing decision-making in companies in the digital era. With the increasing volume, variety, and velocity of consumer-generated data, companies need to leverage big data to understand consumer behavior, identify market trends, and enhance the effectiveness of marketing strategies. This research employs a qualitative descriptive approach using a case study method on several companies that have implemented big data in their marketing decision-making processes. Data were collected through in-depth interviews with marketing managers and data analysts, as well as analysis of internal company documentation related to digital marketing strategies and reports. The results indicate that big data plays a crucial role in improving the accuracy of marketing decisions, enabling more precise market segmentation, and facilitating product offer personalization according to consumer preferences. Companies that integrate big data into their marketing strategies experience increased customer satisfaction, loyalty, and operational efficiency. These findings emphasize that the utilization of big data is a strategic element essential for navigating the dynamics of the digital market and increasingly competitive environment.